Prokopenko A., Shevchenko А. Translation Interpretations of the Pharmaceutical Terms: English-Ukrainian Equivalents - A. V. Prokopenko; A. Shevchenko (Philological Treatises, 2020)
This article deals with the translation interpretations of the pharmaceutical terms, translation features of this terminology, translation difficulties of the pharmaceutical terms and finding its English and Ukrainian equivalents. Nowadays, foreign technologies, equipment and approaches to medicine and in particular, pharmaceutics, are far ahead of domestic production and a large number of drugs are produced abroad. Accordingly, the translation of pharmaceutical texts takes an important place among other types of translation. The pharmaceutical translation does not allow mistakes, the approximate wording and inaccuracies in the interpretation of terms because the distortion of the meaning of the source text can lead to various negative consequences, even can cause harm to health. It is often necessary to use different kinds of translation transformations of pharmaceutical terms because of some differences in the grammatical, syntactic and morphological structures of Ukrainian and English languages. However, the presence of numerous difficulties, namely the Latin and Greek borrowings, the lack of standardization of the pharmaceutical terminology continues to be the main causes of translation errors and a major impediment to sharing information. The abovementioned fact confirms the relevance of this problem. The study of pharmaceutical terminology helps to identify the semantic features that underlie the nomination of new drugs and their methods of use.